The effects of 1a(OH)D3 individually or in combination with phytase, and different levels of cholecalciferol on performance, tibia criteria, and plasma minerals of Japanese quails - Shahab Shams; Farshid Kheiri; Nasir Landy (Acta Scientiarum. Animal Sciences, 2022)
The aim of studywas to compare efficacy of 1-α(OH)D3 alone or in combination with phytase and 1-α(OH)D3 in combination of phytase and different concentration of cholecalciferol on performance, tibia parameters, andplasma minerals of quails fed Ca-P deficient diet. A total of 280 mixed sex 5-d-old quails were allocated to 7 treatments with 5 replicates. The vitamin supplement which incorporated to basal diet did not contain cholecalciferol. The dietary treatments were as follows: Ca-P deficient diet (basal diet); basal diet + 500 FTU phytase/kg of diet; basal diet + phytase + 5 μg of 1-α(OH)D3 kg-1 of diet;basal diet + phytase + 5 μg of 1-α(OH)D3 and 250, 500, 750 and 1,000 IU of cholecalciferol kg-1of diet. The highest final body weight and the best feed conversion ratioobtained in the group supplemented with 1,000 IU cholecalciferol kg-1 of diet (p < 0.05). Supplementation of 1-α(OH)D3 alone or in combination with phytase and phytase and different concentration of cholecalciferol could improve tibia parameters (p < 0.05). In conclusion, supplementation of 1-α(OH)D3 alone to Ca-P deficient diet could maximize tibia mineralization, whereas it couldn't maximize performance, performance criteria were maximized by supplementation of 1,000 IU cholecalciferol kg-1 of diet.